1979
DOI: 10.1007/bf02778832
|View full text |Cite
|
Sign up to set email alerts
|

Implications of reiterative DNA—Metal ion complexes in the induction and development of neoplastic cells

Abstract: Experimental data on the content in metal ions of DNA preparations from various neoplastic and healthy tissues are summarized: metal ions are preferentially bound to reiterative DNA sequences, where they may induce conformational variations and thus modify the binding of effector molecules such as repressors and polymerases.A model is described where essential and toxic metals are successively loaded on ligand acceptor groups of increasing affinity and thus may reach the final active sites: enzymes and reitera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1984
1984
1988
1988

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…This hypothesis is supported by the increase in the highly repetitive fraction found in the transformed strain and by the fact that one of the two additional peaks shown after Ag+-Cs2S04 ultracentrifugation has also been found in the early stages of N. glauca pith tissue proliferation. In our case as in others (GuillC et al, 1979(GuillC et al, , 1981 both tumorous transformations (genetic and epigenetic) were correlated with higher DNA-bound ion content.…”
Section: Discussionsupporting
confidence: 85%
“…This hypothesis is supported by the increase in the highly repetitive fraction found in the transformed strain and by the fact that one of the two additional peaks shown after Ag+-Cs2S04 ultracentrifugation has also been found in the early stages of N. glauca pith tissue proliferation. In our case as in others (GuillC et al, 1979(GuillC et al, , 1981 both tumorous transformations (genetic and epigenetic) were correlated with higher DNA-bound ion content.…”
Section: Discussionsupporting
confidence: 85%
“…The indicated concentrations correspond to the molarity of Zn concentration in one of the two lots the pure metalionin complete medium. The ÷+ ' " of serum used was measured by anodic stripping voltametry (Guille et al, 1979) and found to be 9.1 /.tM. Both sera gave rise to comparable results in the cytotoxicity experiments.…”
Section: Metal Ionsmentioning
confidence: 75%
“…The experiments were carried out with normal mouse fibroblast cells as well as their carcinogen-transformed counterparts. It has been shown that malignant cells bind metal ions to their DNA more efficiently than do normal cells, and that this phenomenon may vary in different species (Andronikashvili et al, 1974;Guille et al, 1979). The toxicity and the mutual interactions of zinc and cadmium are reported here.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…High concentrations of iron have been shown to inhibit the phagocytic activity of monocytes [106] and the tumorcidal action of macrophages [107]. Furthermore, excess iron has been shown to enhance the chromosome damage induced by ascorbate in cultured Chinese hamster ovary cells [109]. It has been theorized that high intracellular iron concentrations could lead to neoplasia by causing conformational variation in reiterative DNA sequences, thus modifying binding of repressors and polymerases, or by leading to a continuous derepression of genes coding for metal ligands [109].…”
Section: The Effect Of Excess Iron On Pathogenesismentioning
confidence: 99%